Great dangers of “small” anesthesia - Yu.O. Olieinikova; O.E. Domoratskyi; V.O. Kryliuk; V.Yu. Gladkykh (Медицина неотложных состояний)
Anesthetic management in various diagnostic and treatment procedures, such as gastroscopy, colonoscopy, hysteroscopy, and others, is aimed at protecting the patient from surgical stress, ensuring psychological comfort, and improving the quality of the procedure. Relative surgical safety, minimal invasiveness, short duration, rarity of anesthetic complications formed the perception of such procedures among patients and a large part of medical workers as absolutely safe. However, anesthetic care during short interventions carries all the dangers of general anesthesia, such as the risk of developing a difficult airway situation, aspiration, hypoventilation, and cardiovascular complications. In the article, the authors consider the current state of the problem of “small” anesthesia in Ukraine.